EFFECT OF SOME CHEMICAL COMPOUNDS ON SOME CHARACTERISTICS OF SHOOT AND FRUIT OF PEACH (Prunus persica L.) CV. EARLY CORONET - Sarfaraz F. A. Al- Bamarny (Mesopotamia Journal of Agriculture)
This study was carried out during 2008 growing season on peach trees (Prunus persica L.) cv. Early Coronet selected from orchard in Seiujh - Duhok city - Kurdistan Region, Iraq, to investigate the effect of [Naphthalene acetic acid [NAA, Riedel-de Haen (0 and 5 mg.l-1); KNO3 (Merck) (0, 0.1 and 0.2 %), and Fe (NaFeEDDHA) Technical Sodium Ferric ethylenediamine di-o-hydroxyphenyle acetate (0, 30 and 60 mg.l-1] on growth and fruit characteristics. One month after fruit set, trees were sprayed at two date (24/April/2008 and 25/May/2008) with NAA, KNO3 and Fe. Raising the levels of NAA to 5 mg.l-1, KNO3 to 0.2 % and Fe to 60 mg.l-1 led to a significant increase in the value of shoot dry weight, total chlorophyll, fruit number, fruit length, fruit diameter, total carotene as compared with untreated trees. The interaction between Foliar spray of 5 mg.l-1 NAA 0.2% KNO3 60 mg.l-1 Fe were the best treatment which gave the highest means of shoot dry weight, total chlorophyll, fruit number, fruit length, fruit diameter and total carotene.